The Influence of Quizizz Media on Students' Learning Motivation in PAI Subjects at Vocational High School - Fikri, Muhammad Shokhiful; Marzuki, Ahmad (-, 2025)
The purpose of this study is to examine the impact of using Quizizz as a learning medium on students’ motivation in vocational high schools. This research employs a quantitative approach with an experimental method using a pre-test and post-test design. Two tests were conducted on the students: one using conventional teaching methods and the other using Quizizz.To collect the necessary data, the study used a research instrument in the form of a questionnaire measured by a Likert scale. Data analysis was conducted using the SPSS application through an Independent Sample T-test. The study involved a sample of 13 students.The results of the analysis showed a significance value of 0.018. Since this value is less than 0.05, it can be concluded that the use of Quizizz has a significant effect on increasing students' learning motivation. In conclusion, Quizizz can be an effective tool to enhance student motivation in Islamic Religious Education subjects at the senior high school and vocational school levels